The Relationship between Internality and Self-development of Psychology Students: the Effect of Optimistic Attributional Style - Ketler-Mytnytska, Tetyana; Shevchenko, Nataliia (Social Welfare: Interdisciplinary Approach, 2022)
The article represents the research of relationship between internality and self-development in the case of the different levels of optimistic attributional styles. The sample consists of psychology students of Ukraine. The strong positive impact of internality on self-development under conditions of medium optimistic attribution has been revealed. A decrease has also been set in self-development of psychology students with high internality in the case of a highly developed optimistic attributional style. It has been established that the psychology students with a medium level of optimistic attributional style and a high level of internality have the highest scores of self-development. The lowest self-development is typical of psychology students with high internality and pessimistic attributional style.
Keywords: self-development; internality; optimistic attributional style; optimism; psychology students